2020
DOI: 10.3390/nano10081472
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Like Layers from Carbon Black: In Vivo Toxicity Assessment

Abstract: Graphene-like (GL) layers, a new graphene-related material (GRM), possess peculiar chemical, colloidal, optical and transport properties. Considering the very recent promising application of GL layers in biomedical and bioelectronic fields, it is of utmost importance to investigate the toxicological profile of these nanomaterials. This study represents an important first report of a complete in vivo toxicity assessment of GL layers on embryonic zebrafish (Danio rerio). Our results show that GL layers do not le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Many studies have reported that CB also has a primary (direct or indirect) genotoxic effect on DNA [ 57 ], and few data are available regarding CB toxicity for bivalves, and these are limited to mussel hemocytes, where oxidative stress and ROS production occurs after in vitro and in vivo exposure [ 58 ]. On the other hand, it is also noteworthy that hydrophilic C-based NPs derived from a high CB destructuration can be regarded as toxicity safe in vivo, since they do not lead to any perturbations of different biological parameters on the vertebrate model Danio rerio [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that CB also has a primary (direct or indirect) genotoxic effect on DNA [ 57 ], and few data are available regarding CB toxicity for bivalves, and these are limited to mussel hemocytes, where oxidative stress and ROS production occurs after in vitro and in vivo exposure [ 58 ]. On the other hand, it is also noteworthy that hydrophilic C-based NPs derived from a high CB destructuration can be regarded as toxicity safe in vivo, since they do not lead to any perturbations of different biological parameters on the vertebrate model Danio rerio [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biological effects, mechanisms of the action and toxicity exerted by GRMs are almost unexplored and a clear categorization of the structure-activity relationships (SARs) is still far from being achieved. So far, only few publications on the biological effects of GRMs on living cells have been published [ 38 , 39 , 40 ]. In addition, the wide variability of GRMs in terms of structure, composition and properties (even within the same GRM category) opens the door to controversial biological effects in both in vitro and in vivo contexts [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The quality and the characteristics of biomass-derived graphene-like materials are highly dependent on the precursor and the manufacturing technique. Graphene-like materials obtained from a controlled top-down demolition of a nanostructured carbon black (CB) in which they are embedded [ 51 , 52 ] are nanometric sized graphene stacked layers and exhibit peculiar chemical-physical properties and promising bio-safety (differently from the most GRMs) [ 40 , 53 , 54 , 55 , 56 ], forecasting feasible applications in many fields including bioelectronics, sensing and functional coatings. The synthetic approach offers control of the product’s relevant chemical-physical features, and it is suitable for bulk production.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations